Correlates of children's sympathy: Recognition and regulation of sadness and anger. Issue 3 (9th December 2021) - Galarneau, Emma; Colasante, Tyler; Speidel, Ruth; Malti, Tina
Abstract: Emotion recognition and emotion regulation have been implicated as promising correlates of sympathy. However, their relative and joint contributions to sympathy in different periods of childhood remain unclear. Moreover, researchers have not explored the relative importance of recognizing and regulating distinct distress‐related emotions, such as sadness and anger, for sympathy. The objective of the current paper was to gain a deeper understanding of which underlying emotion‐related factors are most implicated in sympathy and when in childhood they are most predictive. With an ethnically diverse sample of 4‐ and 8‐yearolds ( N = 300, n = 150 in each age group; 50% female), this study tested sadness and anger recognition and regulation, and interactions thereof, as predictors of sympathy. Better sadness and anger regulation independently predicted higher levels of sympathy in 4‐ and 8‐year‐olds, albeit sadness regulation was a more robust predictor of sympathy in 4‐year‐olds. Better sadness recognition was associated with higher sympathy in 8‐year‐olds who also had better sadness regulation. Results underscore the importance of emotion regulation for sympathy, particularly in early childhood. The findings also tentatively suggest that the correlates of sympathy may become more nuanced in middle childhood, with emotion‐specific recognition and regulation capacities employed in concert.